Cloud web server for IoT smart laboratory system - Lee, Yi Ming (2022)
The IoT (Internet of Things) technology is experiencing tremendous growth as the connectivity expands across the world, and it keeps on breaking the boundaries on showing what advanced technology can do. Most of the laboratories lack IoT technology and still pay a high cost to ensure security. In the very common scenario, the appliances of the laboratory such as lights and air conditioners are kept left on, even when not in use. It leads to a rise in power consumption and wastage of energy in the laboratory. Therefore, this proposed project aims to develop a cost-effective and reliable IoT-based smart laboratory system that reduces power consumption, strengthened security, and provides convenience for users to control laboratory appliances even at a distance. MQTT protocol is the communication between the server and client to publish and subscribe to the data. This system utilizes NodeMCU to connect several different sensors and transfer their data to the Raspberry Pi local server using Wi-Fi protocol. It will then send it to cloud server. It enables users to stay connected with the laboratory from time to time by accessing the user-friendly interface website through smartphones or laptops. The real-time collected data will be displayed on the dashboard developed in Node-RED. The proposed smart laboratory system intends to efficiently control appliances using the Internet with the convenience of checking data from the website anytime, anywhere.